2003
DOI: 10.1034/j.1399-0004.2003.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Gaucher's disease: identification of novel mutant alleles and genotype–phenotype relationships

Abstract: A sequencing protocol for the acid beta-glucosidase (GCase) gene (GBA) was developed using a long-range PCR template. This protocol has an advantage of greater DNA yields over similar strategies. Seven Gaucher's disease patients had four novel and five other rare alleles. A non-pseudogene in-frame deletion (g.2600-2602delTAC) and a new complex mutation (null allele) were identified in Gaucher's disease type 1, i.e. the g.2600-2602delTAC deletion is associated with the non-neuronopathic variant. An F251L allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…However, compound heterozygosity with G202R/E326K and L444P/ E326K genotypes and half-normal GCase activity levels indicated that normalcy for periods of 1-4 decades can exist in the presence of an E326K allele (36). Interestingly, the E349K GCase and E326K are approximately equally spaced from the active site in the crystal structure, but E349K had much greater effects on the CRIM specific activity and other enzymic properties than did E326K.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compound heterozygosity with G202R/E326K and L444P/ E326K genotypes and half-normal GCase activity levels indicated that normalcy for periods of 1-4 decades can exist in the presence of an E326K allele (36). Interestingly, the E349K GCase and E326K are approximately equally spaced from the active site in the crystal structure, but E349K had much greater effects on the CRIM specific activity and other enzymic properties than did E326K.…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ to ϩ). This variant has been found in phenotypically normal individuals as the heteroallele to L444P-or G202R-encoding alleles (36). The ⌬36 GCase, an in-frame codon deletion of threonine 36, could be partially purified in the presence of mixture III, and that enzyme had significant CRIM specific activity (ϳ35% of wild-type).…”
Section: Mutations Point Substitutions and Characteristics Of Mutantmentioning
confidence: 93%
“…While initially reported as single disease-causing mutations Eyal et al, 1991], two specific alterations, c.1093G4C (E326 K) and c.1223C4T (T369 M), have been found in patients primarily in cis with other identified mutations Walker et al, 2003] and have lead to published corrections after identification of a second mutation on the same allele [Torralba et al, 2001a[Torralba et al, , 2001b. Zhao et al [2003b] reported a family in which a c.1093G4C allele was found in two unaffected individuals who carried either c.721G4A (G202R) or c.1448T4C (L444P) on their second allele. Neither of the two affected individuals in this family had the c.1093G4C alteration.…”
Section: Recombinant and Complex Allelesmentioning
confidence: 99%
“…Specifically, there seems to be two major expressions of this phenotype; one with major visceral involvement and a second with late-onset progressive myoclonic seizures from progressive CNS disease. This segregation of phenotypes 22 serves a useful purpose in descriptions of such phenotypes throughout the world, but a continuum of neurologic phenotypes populate the spectrum between these descriptors. 12 In the ethnic Polish population, the skeletal involvement in patients with severe visceral disease has greater similarity to that described in the Swedish population than in other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The above group is similar to that described as type 3a. 22 The larger type 3 group (13 individuals) developed neurologic signs later. Supranuclear gaze paresis usually predominates; massive hepatosplenomegaly, wasting, and progressive skeletal abnormalities are characteristic.…”
Section: Patient Characteristicsmentioning
confidence: 99%